1990
DOI: 10.1002/jat.2550100509
|View full text |Cite
|
Sign up to set email alerts
|

Toxicology and carcinogenicity studies of diuretics in F344 rats and B6C3F1 mice 1. Hydrochlorothiazide

Abstract: Toxicology and carcinogenesis studies of hydrochlorothiazide, a benzothiadiazide diuretic, were conducted by administering diets containing the drug to both sexes of F344 rats and B6C3F1 mice in 15-day, 13-week and 2-year studies. No rats died during the 15-day or 13-week studies at dietary concentrations of up to 50,000 ppm. Deaths of male mice in the top dose group in the 13-week study were likely to be related to chemical administration. In the prechronic studies, increased nephrosis and mineralization at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0
2

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 35 publications
1
10
0
2
Order By: Relevance
“…Thus the exacerbation seems not to be synergistic but additive, taking into account the incidences and grades of CPN in rats treated with 1625 mg/kg/day OM/HCTZ, 1000 mg/kg/ day OM and 625 mg/kg/day HCTZ. Although HCTZ alone exacerbated CPN in this study as reported by other researchers (Bucher et al, 1990;Lijinsky and Reuber, 1987), HCTZ is one of the major diuretics in the market and is, in general, considered safe rather than nephrotoxic (Jackson, 2001). In addition, exacerbation of CPN was observed in rats given 48.75 mg/kg/ day OM/HCTZ or more and these doses were higher than pharmacologic dose (1-10 mg/kg/day in Spontaneously hypertensive rats, non-published data).…”
Section: Discussionsupporting
confidence: 72%
“…Thus the exacerbation seems not to be synergistic but additive, taking into account the incidences and grades of CPN in rats treated with 1625 mg/kg/day OM/HCTZ, 1000 mg/kg/ day OM and 625 mg/kg/day HCTZ. Although HCTZ alone exacerbated CPN in this study as reported by other researchers (Bucher et al, 1990;Lijinsky and Reuber, 1987), HCTZ is one of the major diuretics in the market and is, in general, considered safe rather than nephrotoxic (Jackson, 2001). In addition, exacerbation of CPN was observed in rats given 48.75 mg/kg/ day OM/HCTZ or more and these doses were higher than pharmacologic dose (1-10 mg/kg/day in Spontaneously hypertensive rats, non-published data).…”
Section: Discussionsupporting
confidence: 72%
“…In the present study, the body potassium deficit is unknown; serum potassium concentration was decreased by 13% (3,4). The reason for the apparent lack of RPCG is unknown, but it may be due to the maintenance of medullary potassium concentration in animals treated with these diuretics, or other factors.…”
Section: Discussionmentioning
confidence: 57%
“…However, with the rapid advances that have been made in elucidating the pathogenesis of cardiovascular diseases through cellular and molecular methods, it has become evident that hypertension, atherosclerosis, and cancers share, to some extent, similar cellular and molecular characteristics [23][24][25]. Studies carried out in animals indicate that the diuretic drugs hydrochlorothiazide and furosemide may have a carcinogenic effect on the kidney [26,27], as well as on other organs, although the effect is probably of small magnitude. In a recent thorough meta-analysis, diuretic therapy was associated with risk of renal cell carcinoma when compared with patients not on diuretics [28].…”
Section: Discussionmentioning
confidence: 95%